Test Control in the Process of Teaching Russian as a Foreign Language - STAROSTINA, O.V.; CHUMAKOVA, G.V.; PETROVA, S.M. (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The article is devoted to the problems of studying the functions of test control, the role of results studies in the adjustment of training content. The information processing work based on the results of testing helps to identify both universal difficulties and lexical-grammatical and speech material. The study aimed to find out the relation between the results of comparative linguistic analysis, the systematization of mistakes in testing, and the achievement of the main purpose of training. It is concluded that the test control always has a training character in the broad sense of the term.RESUMEN El artículo está dedicado a los problemas de estudiar las funciones del control de pruebas, el papel de los estudios de resultados y el ajuste del contenido de la capacitación. El trabajo de procesamiento de información basado en los resultados de las pruebas ayuda a identificar dificultades universales y léxico-gramaticales. El objetivo del estudio fue descubrir la relación entre los resultados del análisis lingüístico comparativo, la sistematización de errores en las pruebas y el logro del objetivo principal de la capacitación. Se concluye que el control de prueba siempre tiene un carácter de entrenamiento en el sentido amplio del término.